Research on political and economic transition in Mali : unfinished state - (:unkn) unknown (My University, 2016)
This thesis is both critical and pragmatic. A criticism of Mali’s recent history read in the light of the tools provided by the legal analysis, sociology and anthropology of law. This critical intent led to examine the history of Mali’s origins in a genetic perspective that has been detailed in the prolegomena. Pragmatic, the thesis puts forward proposals related to the concrete situation of Mali, along the lines of a deregulation of consciences and the re-introduction of constitutive standards into the Malian Republic. The language analysis proved valuable in meeting these two requirements. They also enabled to identify some shortcomings in legal dogma generally more anxious to graft prefabricated concepts onto African realities, rather than capture these realities with their nuances as close as possible. It therefore seemed appropriate to analyze the strategies of ordinary actors of the Malian political society. The consideration of the concepts handled by these latter accounts for the use of indigenous languages. The first part of the thesis is devoted to the analysis of Mali’s chaotic development in the aftermath of the relinquishment of the fathers’ project of independence under the double pressure of economic constraints and cultural determinants. The second part draws the relevant consequences from the point of view of constitutional theory. Thus, the thesis concludes with the proposal for reform of the system of African Unity based, upon as all the above, Bambara language’s saying : “Sleeping on the mat of others is like sleeping on the floor.
Keywords: African Research